Within and Beyond Mimetic Desire - Di Blasi, Luca (Mimesis, desire, and the novel, 2015)
René Girard does not make it easy to do him justice. His pronounced hermeneutics of suspicion easily mobilizes suspicion against his own writings. He appears sometimes enlightening and even wise, sometimes provocative and single-minded. While the monocausal redundancy of his explanations tempts his readers to underestimate him, the coherence of his work and the striking simplicity and plausibility of many of his explanations command respect and admiration. It seems to me that at least some of these tensions are consequences of some major contradictions in Girard’s work. Th ey refer to his key notion of mimetic desire and its constitutive